Stages of development and determination of the cost of development of regulatory environmental documentation on transport - Skorev Michail; Kirishchieva Irina; Zhigunova Anna; Kirishchieva Viktoria (E3S Web of Conferences, 2023)
The requirements of modern nature management imply mandatory compliance with environmental legislation aimed primarily at eliminating problems in the field of environmental protection. The primary measure in this direction is the development by economic entities of environmental documentation reflecting the main provisions of environmental activities. Management processes at the level of economic entities involve activities related to environmental protection, which is subject to mandatory documentation through the development of regulatory environmental documentation. Identifying the stages of this type of activity allows you to clearly understand the sequence of work in terms of the development of regulatory environmental documentation and properly organize management processes in this area. In addition, it should be taken into account that often the cost of developing such documentation is unacceptable for enterprises of various fields of activity, therefore, this article discusses the main individual postulates of the formation of such documentation and determining its cost both at the stage of a commercial offer and at the stage of concluding a contract for the development of environmental documentation.